2021
DOI: 10.1186/s12978-021-01273-x
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum intrauterine contraceptive device use and its associated factors in Ethiopia: systematic review and meta-analysis

Abstract: Background The intrauterine contraceptive device, a type of long-acting reversible contraception, is one of the most effective and safe contraceptive methods. In Ethiopia, intrauterine contraceptive device is little known and practised to delay pregnancy. Therefore, this study aimed to assess post-partum intrauterine contraceptive device utilisation and its associated factors among women in Ethiopia. Method In the current meta-analysis, variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…The prevalence of IPPIUCD utilization in this study was 22.1% (95% CI: 17.3 – 25.2), which was consistent with studies done in North Shoa (21.3%), 20 Sidama, (21.9%), 17 and pooled prevalence in Ethiopia (21.6%). 21 However, it was higher than the studies conducted in Uganda (16.3%), 22 Bale zone (12.4%), 23 Bahir Dar (13.3%), 24 and Debre Tabor (3.3%), Ethiopia. 25 These variations might be due to differences in sociocultural and demographic characteristics, and the number of facilities involved in the study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The prevalence of IPPIUCD utilization in this study was 22.1% (95% CI: 17.3 – 25.2), which was consistent with studies done in North Shoa (21.3%), 20 Sidama, (21.9%), 17 and pooled prevalence in Ethiopia (21.6%). 21 However, it was higher than the studies conducted in Uganda (16.3%), 22 Bale zone (12.4%), 23 Bahir Dar (13.3%), 24 and Debre Tabor (3.3%), Ethiopia. 25 These variations might be due to differences in sociocultural and demographic characteristics, and the number of facilities involved in the study.…”
Section: Discussionmentioning
confidence: 68%
“…This is comparable with the study done in Addis Ababa, 19 and meta-analysis finding in Ethiopia. 21 This could be because mothers who had good knowledge about PPIUCD may have better practice and they are more likely to use the method consistently and effectively than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…A person whose age was between 20 and 24 years old were 2.38 times more likely to utilized SRH service compared to age less than 20 years old. This is supported by a systematic review and meta-analysis conducted in Ethiopia before covid 19 pandemic (15,17). This could be potentially explained by individuals above age 20 has a chance to hear about the SRH service utilization from different medias and electronic web sites.…”
Section: Discussionmentioning
confidence: 77%
“…Met analysis from African regions have detailed in their systematic reviews that the prevalence of acceptance PPIUCD utilization within Ethiopian women was 21.63% and ranged between 14.46% to 28.81%. 12 Similarly, a meta-analysis research conducted in Uganda and Sub Saharan Africa also reported then antennal counselling outcomes with an uptake of PPIUCD with a prevalence of 16.3% and 41.2% respectively 13,14 . It has proven that if a contraceptive method is provided prior to hospital discharge then there is a high reduction in unwanted pregnancies and subsequently decreases in mother and child life threatening outcomes.…”
Section: Discussionmentioning
confidence: 95%